Examining the Influence of Administrative Team, Leadership Skills, and Sports Management Support on National Team Performance: Insights from Qatar - Al-Jael, Mana Ahmed Mana; El-Gohary , Hatem (Journal of Ecohumanism, 2024)
This study explores how administrative team skills, leadership support, ongoing training, and high-level leadership influence the sports performance of Qatari national teams. A quantitative approach was used, beginning with a review of previous research, followed by data collection through a questionnaire. The research sample included 131 individuals holding various administrative and technical roles within the administrative team of Qatari national teams. The reliability and validity of the questionnaire were confirmed using Cronbach's alpha, ensuring the data was suitable for statistical analysis. The study findings indicate a strong and statistically significant correlation between administrative skills and sports performance, emphasising the importance of developing these skills to improve team outcomes. Training also showed a considerable positive impact on performance, reinforcing the role of continuous development in enhancing players' abilities. Ongoing qualification of the administrative team emerged as a key factor in increasing efficiency and improving performance. Administrative support was found to be a critical mediator that strengthens the relationship between administrative skills, training, qualification and sports performance. Its role enhances the effectiveness of these factors and maximises their impact. The study also highlights how administrative support significantly bolsters the connection between leadership skills and sports performance, underscoring its role in achieving superior results. Based on these findings, the study presents practical recommendations for improving sports performance through skill development and continuous training. Understanding the internal environment and setting clear objectives are essential steps. Additionally, educating team members in sports marketing is recommended to strengthen strategic approaches within national teams.